Suatu penerokaan awal mengenai pendekatan tasawuf terhadap agama-agama lain - Yusri Mohamad Ramli,; Mohd Syukri Yeoh Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
There would be no doubt that the Sufis is the only Muslim group within and whithout that firmly and constantly expound their conception on religious pluralism. Hence, it is not surprised to see many of their extravagant stanzas oftenly quoted by current preachers of love to bridge connection between religions. Moreover, their way of approaching to other religions is eccentricly emphatic and inclusive. This article attemps to analyse selected anecdotes, utterances, and stanzas of the Sufis related to religion and its plurality in order to grasp the general ideas of their approach to other religions. This study found that their extreme tolerance of the others does not impede them from being consistent with Islam. Furthermore, it is regarded as the uttermost paths to grasp and realise the oneness of God. Apart from being a brief presentation for my doctoral research, this piece of preliminary investigation aimed to better comprehend the Sufi conception of religious pluralism and their attitude towards the others.